2010
DOI: 10.1585/pfr.5.039
|View full text |Cite
|
Sign up to set email alerts
|

Deepening of Floating Potential for Tungsten Target Plate on the way to Nanostructure Formation

Abstract: Deepening of floating potential has been observed on the tungsten target plate immersed in high-density helium plasma with hot electron component on the way to nanostructure formation. The physical mechanism is thought to be a reduction of secondary electron emission from such a complex nano fiber-form structure on the tungsten surface. Tungsten material is very important in terms of fusion reactors, especially plasma-facing component. Helium defects are the concerns when employing the tungsten for the diverto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 9 publications
1
15
0
Order By: Relevance
“…author's e-mail: takamura@aitech.ac.jp surface temperature of 1420 K. The tungsten is made with cold-worked powder metallurgy. The helium plasma condition in AIT-PID (Aichi Institute of Technology -Plasma Irradiation Device) is similar to that in the previous report [4]. The experiment of temperature excursion in helium plasma [5] has shown a shortening and a fattening of originally long and thin nano fibers when the surface temperature increases up to 1600 K for a few minutes.…”
Section: Recovery Of Tungsten Surface With Fiber-form Nanostructure Bsupporting
confidence: 52%
“…author's e-mail: takamura@aitech.ac.jp surface temperature of 1420 K. The tungsten is made with cold-worked powder metallurgy. The helium plasma condition in AIT-PID (Aichi Institute of Technology -Plasma Irradiation Device) is similar to that in the previous report [4]. The experiment of temperature excursion in helium plasma [5] has shown a shortening and a fattening of originally long and thin nano fibers when the surface temperature increases up to 1600 K for a few minutes.…”
Section: Recovery Of Tungsten Surface With Fiber-form Nanostructure Bsupporting
confidence: 52%
“…where φ work is the work function of the employed metal, γ ion is the ion-induced electron emission coefficient and γ e is the SEE one on the W surface due to energetic electrons, while γ e from bulk electrons may be neglected In fact, a virgin W has a fairly high SEE [13] and a very large ion-induced electron emission [14] including the kinetic as well as Auger effects, while the nanostructured W suppresses those electron emissions due to deep valleys associated by the formation of fiber-form nanostructure [7,15,16]. Each electron emission from metal surface extracts the thermal energy of the metal corresponding to, at least, work function, 4.5 eV for W.…”
Section: Comparison Between Experiments and Modified Ptf Theorymentioning
confidence: 99%
“…One of the PWI studies is the fiber‐form nanostructure formation on a tungsten (W) surface [5–11]. This is one of the He defects on W at a relatively low surface temperature, i.e., below about 1500 K. Another He defect is the formation of bubbles/holes on the W surface at a surface temperature higher than 1600 K. Preliminary results on such PWI studies in the AIT‐PID have been reported [12].…”
Section: Example Of Pwi Experimentsmentioning
confidence: 99%
“…We can recognize a forest‐like appearance made of very thin fiber‐form W. Many researches have started using the present facility of AIT‐PID. The suppression of secondary electron emission was demonstrated by utilizing the presence of the hot‐electron component in this device [9]. The recovery of W surface with fiber‐form nanostructure has been tried in the Ar discharge plasma in AIT‐PID [10].…”
Section: Example Of Pwi Experimentsmentioning
confidence: 99%
See 1 more Smart Citation